Symptomatic Secondary Selective IgM Immunodeficiency in Adult Man with Undiagnosed Celiac Disease - Eli Magen; Viktor Feldman; Mishal Joseph; Hadari Israel (Case Reports in Immunology)
Selective IgM immunodeficiency (SIgMID) is a heterogeneous disorder with no known genetic background and may occur as a primary or a secondary condition. Celiac disease has been reported in association with several humeral immunodeficiencies, including isolated severe selective IgA deficiency, panhypogammaglobulinemia, and isolated combined IgA and IgM deficiency. There are only few reported cases of pediatric and adult patients with SIgMID and celiac disease. In this paper, we describe an adult patient with a symptomatic secondary SIgMID associated with undiagnosed celiac disease, with a resolution of clinical symptoms of immunodeficiency and serum IgM normalization following a gluten-free diet.